Using a spend analysis to help identify prospective Air Force purchasing and supply management initiatives : summary of selected findings - Moore, Nancy Y., 1947-; Cook, Cynthia R., 1965-; Lindenblatt, Charles (Charles A.); Grammich, Clifford A. (Clifford Anthony), 1963-; Rand eBooks (Santa Monica, CA : RAND, 2004)
This briefing summarizes research on how the Air Force might use an analysis of its spending to develop better supply strategies, improve its relationships with suppliers, and better manage its supply base. Best practices offer many ways by which the Air Force can improve performance and save money. Such techniques include consolidating multiple contracts with existing providers, selecting the best providers and offering them longer contracts with broader scopes of goods and services, and working with selected strategic partners to improve quality, responsiveness, reliability, and cost. There are many challenges to conducting an Air Force-wide spend analysis, primarily the lack of detailed, centralized data on all expenditures as well as questions about data quality for those data that are available. Nevertheless, the data that do exist point to many prospective sources of savings and performance improvements. The authors analyze the most complete centralized source available on Air Force expenditures, known as DD350 data. Transactions in the DD350 data constitute 96 percent of all Air Force contract dollars spent directly. Among the actions that the Air Force might wish to take are: consolidation of a large number of contracts with similar or the same supplier; grouping contractor ID codes having multiple contracts with the Air Force and many purchase office codes associated with the same contractor, so that the Air Force does not have to pay for the contractor's repetitive bidding and contract administration costs; examining contracts for goods or services available from only one supplier, which gives the Air Force only limited opportunities to gain leverage over such suppliers. Conducting a detailed Air Force spend analysis would require information on the needs, preferences, and priorities of commodity users not available in the DD350 data. Because the Air Force needs to balance prospective savings, performance improvements, risks, socioeconomic and other goals, and other regulations not always present in the private sector, not all best commercial practices may be appropriate for it.
Introduction -- Overview of Spend Analysis -- Indicators to Target Prospective PSM Initiative -- Insights for Specific PSM Improvements -- Lessons for the Air Force -- Appendix: Lessons Learned in Using DD350 Data for DoD Spend Analyses
"April 2004."
"Project Air Force."
Includes bibliographical references (p. 85-89).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Air Force -- Appropriations and expenditures -- Evaluation; United States. -- Air Force -- Materials management; United States. -- Air Force -- Procurement; Defense contracts -- United States; Electronic books